Optimizing initial biomass to enhance microplastic sequestration via density-driven bio-flocculation in microalgal systems - Xiaoxue Mei; Jiawei Wang; Xueying Zhao; Yilu Liang; Baiyun Lu; Yawen Fan; Defeng Xing; Nanqi Ren; Yan Liu (Bioresource Technology, 2026)

Direct evidence of particle-phase reactions of aldehydes and ketones with atmospheric secondary organic aerosol components - Siqi Tang; Yindong Guo; Xiaolei Yang; Zhen Song; Yali Jin; Shuhui Xue; Jianghe Xiong; Defeng Zhao (Atmospheric Environment, 2026)

Phthalate esters in cooking organic aerosols from various edible oils - Xiaolei Yang; Shuhui Xue; Qingpeng Meng; Siqi Tang; Chunlin Li; Lina Wang; Defeng Zhao (Journal of Environmental Sciences, 2026)

Evaluation of an Automated Vaccination Strategy Against Aeromonas hydrophila in Grass Carp: A Comparative Study with Conventional Manual Injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Jian Zhao; Songming Zhu; Zhangying Ye (Fishes, 2026)
(1) Background: Vaccination is crucial for Ctenopharyngodon idella, yet the impact of delivery methods on welfare and immunity requires investigation. (2) Methods: This study compared manual (HI-V) and automated (AI-V) injections of inactivated Aeromonas hydrophila vaccine. (3) Results: Both methods induced protective immunity, with AI-V achieving a slightly higher Relative Percent Survival (41.67%) than HI-V (37.84%). AI-V promoted stable erythropoiesis and robust systemic/mucosal IgM responses with elevated HSP70 and IL-6. Conversely, HI-V triggered sharp transient stress and upregulated Gadd45γ, indicating greater genotoxic stress. (4) Conclusions: Automated injection offers comparable immune protection with reduced physiological stress and improved homeostasis, supporting its use for welfare-conscious aquaculture.

Sesquiterpenoids from Euphorbia esula L. - Defeng Yan; Miaomiao Zhang; Dan Tang; Yuqing Song; Liu Liu; Haiqing Zhao; Nurmirza Begmatov; Orzimat Turdimatovich Turginov; Bo Zhao; Hequn Yang; Guoan Zou (Phytochemistry, 2026)

Flume investigation of the breach process of rock-avalanche dam characterized by a coarse carapace layer - Tingkai Nian; Dongyang Li; Hao Wu; Rundong Zhao; Defeng Zheng (Natural Hazards, 2026)

Elastic conductive polyurethane/PEDOT:PSS composite with self-healing and closed-loop recyclability - Wei-Chen Gao; Ben Fan; Junmei Hu; Yu-Dong Zhao; Xiang Sun; Defeng Cui; Jing Qiao; Wei-Bing Lu; Ying-Shi Guan (Chemical Engineering Journal, 2025)

Energetic photoexcited electrons and enhancement of metabolic function and electron transport promote carbon chain elongation in bacterium‑cadmium sulfide biohybrid systems - Huize Fan; Jing Wang; Xiaoxue Mei; Baiyun Lu; Lei Zhao; Nanqi Ren; Defeng Xing (Chemical Engineering Journal, 2025)

Altered functional connectivity within and between resting-state networks in ulcerative colitis - Yanjun Ren; Kaizhong Xue; Huijuan Xu; Lijie Hao; Quchuan Zhao; Tianyu Chi; Hongwei Yang; Xiaojing Zhao; Defeng Tian; Huihong Zhai; Jie Lu (Brain Imaging and Behavior, 2025)

The generation and transformation mechanisms of reactive oxygen species in the environment and their implications for pollution control processes: A review - Zhihao Bi; Wei Wang; Lei Zhao; Xueting Wang; Defeng Xing; Yanfeng Zhou; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Environmental Research, 2024)

Linking performance to dynamic migration of biofilm ecosystem reveals the role of voltage in the start-up of hybrid microbial electrolysis cell-anaerobic digestion - Xue-Ting Wang; Lei Zhao; Quan Zhang; Bo Wang; Defeng Xing; Jun Nan; Nan-Qi Ren; Duu-Jong Lee; Chuan Chen (Bioresource Technology, 2024)

Mechanisms of metabolic regulation and enhanced methane production by hydrolytic nanozyme in sludge anaerobic digestion - Jing Wang; Cai Yan; Zheng Zhong; Baiyun Lu; Chuan Chen; Lei Zhao; Jun Ma; Defeng Xing (Chemical Engineering Journal, 2024)

Effects of long-term warming on soil prokaryotic communities in shrub and alpine meadows on the eastern edge of the Qinghai-Tibetan Plateau - Wei Li; Lingchen Yuan; Xianli Lan; Rui Shi; Dongdong Chen; Defeng Feng; Xinquan Zhao; Huai Chen (Applied Soil Ecology, 2023)

Co-treatment with free nitrous acid and calcium peroxide regulates microbiome and metabolic functions of acidogenesis and methanogenesis in sludge anaerobic digestion - Jing Wang; Yu Lou; Dongmei Ma; Kun Feng; Chuan Chen; Lei Zhao; Defeng Xing (Science of The Total Environment, 2023)

Do ectoparasites on fish gills “talk” with gut microbiota far away? - Lin Wang; Defeng Zhang; Jun Xie; Ouqin Chang; Qing Wang; Cunbin Shi; Fei Zhao; Hua Gong; Yan Ren; Najiah Musa; Kok Leong Lee; Houjun Pan (Aquaculture, 2023)

MSINGB: A Novel Computational Method Based on NGBoost for Identifying Microsatellite Instability Status from Tumor Mutation Annotation Data - Jinxiang Chen; Miao Wang; Defeng Zhao; Fuyi Li; Hao Wu; Quanzhong Liu; Shuqin Li (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Comparison of Anaerobic Methane Oxidation in Different Sediment Habitats of Dianchi Lake - Wei Li; Yue Chen; Mingmo Luo; Chunyan Li; Yonggui Zhao; Huai Chen; Defeng Feng; Bin Hu (Water, Air, & Soil Pollution, 2020)

Ecosystem carbon stock across a chronosequence of spruce plantations established on cutovers of a high-elevation region - Xueyong Pang; Junsheng Huang; Qingxia Zhao; Defeng Feng; Weikai Bao; Guanglong Tian (Journal of Soils and Sediments, 2017)

Controllable synthesis Fe3O4@POHABA core-shell nanostructure as high-performance recyclable bifunctional magnetic antimicrobial agent - Zhijia Zhang; Defeng Xing; Xin Zhao; Xiaojun Han (Environmental Science and Pollution Research, 2017)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Water resource utilization efficiency and spatial spillover effects in China - Caizhi Sun; Liangshi Zhao; Wei Zou; Defeng Zheng (Journal of Geographical Sciences, 2014)

Microbial community structure of ethanol type fermentation in bio‐hydrogen production - Nanqi Ren; Defeng Xing; Bruce E. Rittmann; Lihua Zhao; Tianhui Xie; Xin Zhao (Environmental Microbiology, 2007)
Summary Three continuous stirred‐tank reactors (CSTRs) were used for H 2 production from molasses wastewater at influent pH of 6.0–6.5 (reactor A), 5.5–6.0 (reactor B), or 4.0–4.5 (reactor C). After operation for 28 days, the microbial community formed ethanol type (C), propionate type (A) and ethanol‐butyrate‐mixed type (B) fermentation. The H 2 production rate was the highest for ethanol type fermentation, 0.40 l (g VSS) −1 day −1 or 0.45 l H 2 (g COD removed) −1 . Microbial community dynamics and diversity were analysed using double‐gradient denaturing gradient gel electrophoresis (DG‐DGGE). Denaturing gradient gel electrophoresis profiles indicated that the community structures changed quickly in the first 14 days. Phylogenetic analysis indicated that the dominant bacterial groups were low G+C Gram‐positive bacteria, Bacteroides , γ‐Proteobacteria and Actinobacteria ; α‐Proteobacteria , β‐Proteobacteria , δ‐Proteobacteria and Spirochaetes were also presented as minor groups in the three reactors. H 2 ‐producing bacteria were affiliated with Ethanoligenens , Acetanaerobacterium , Clostridium , Megasphaera , Citrobacter and Bacteroides. An ethanol‐based H 2 ‐producing bacterium, Ethanoligenens harbinense CGMCC1152, was isolated from reactor C and visualized using fluorescence in situ hybridization (FISH) to be 19% of the eubacteria in reactor C. In addition, isoenzyme activity staining for alcohol dehydrogenase (ADH) supported that the majority of ethanol‐producing bacteria were affiliated with Ethanoligenens in the microbial community.